Historie van het huis van Adriaan: Eene grappige vertelling - Anonymous (Salt Lake City, UT : Project Gutenberg, 2016)
"Historie van het huis van Adriaan: Eene grappige vertelling" by Anonymous is a humorous children$1 (Bs story likely written during the late 19th century. The book employs a repetitive and cumulative narrative style that illustrates the interconnections among various animals and characters associated with the titular house of Adriaan. Its likely topic revolves around everyday rural life and the simple interactions between humans and animals in a whimsical context. The story unfolds in a playful manner, detailing a chain of events that begins with grain in the house of Adriaan and progresses through a series of characters, including a rat, a cat, a dog, a cow, a daughter, a rooster, a fox, and a young boy named Filip. Each character is connected by their roles in the unfolding action, where they interact with one another in humorous and exaggerated ways. The rhythmic and repetitive nature of the narrative creates a lively and engaging experience for children, emphasizing moral lessons about community and family life in a light-hearted fashion. (This is an automatically generated summary.)s
Release date is 2016-05-15
Produced by Jeroen Hellingman.
Keywords: Nursery rhymes; Children's poetry, Dutch